1994
DOI: 10.1002/bjs.1800810221
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography as a method of measuring breast tumour size and monitoring response to primary systemic treatment

Abstract: Accurate measurement of change in tumour size is a prerequisite for the use of response-based regimens of primary systemic therapy for breast cancer. This study evaluated the accuracy of clinical assessment, mammography and ultrasonography in measuring tumour size and in monitoring response to treatment. Size was determined during the week preceding surgery and actual size measured from resected specimens. Sequential measurements were performed in 35 patients undergoing primary systemic treatment. There was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 20 publications
0
27
1
3
Order By: Relevance
“…Previous studies comparing clinical, mammographic or ultrasound assessment with maximal histological diameter of the tumour have demonstrated no difference between the modalities (Pain et al, 1992), although others have shown ultrasound to be better (Fornage et al, 1987;Forouhi et al, 1992). In our study, ultrasound and mammography gave substantially lower response rates than did clinical examination.…”
Section: Discussioncontrasting
confidence: 57%
“…Previous studies comparing clinical, mammographic or ultrasound assessment with maximal histological diameter of the tumour have demonstrated no difference between the modalities (Pain et al, 1992), although others have shown ultrasound to be better (Fornage et al, 1987;Forouhi et al, 1992). In our study, ultrasound and mammography gave substantially lower response rates than did clinical examination.…”
Section: Discussioncontrasting
confidence: 57%
“…Serial measurements of the primary tumours were taken before, at 6 weeks and at 3 months by calliper and ultrasound as described previously (Forouhi et al, 1994;Dixon, 2001). The tumour was also imaged mammographically before and at 3 months.…”
Section: Treatmentmentioning
confidence: 99%
“…Tumour volumes were determined from ulstrasound measurements as described by Forouhi et al (1994). Reduction in volume over a 3 month period 450% was regarded as clinical response; this includes both complete and partial responders.…”
Section: Response Assessmentmentioning
confidence: 99%
“…Ultrasound measurement of three orthogonal tumour diameters produced an estimate of tumour volume. Reduction in tumour volumes 425% was regarded as evidence of tumour response; those 450% were categorised as major response (Forouhi et al, 1994).…”
Section: Clinical Responsementioning
confidence: 99%